Stink Bugs in Florida Rice - Ron Cherry (EDIS)
Although many different insects can be found in rice fields in Florida, stink bugs are currently considered the most important pest. Jones and Cherry reported that the rice stink bug was the dominant species, comprising more than 95% of the total stink bug population. Cherry et al. (1998) reported that the stink bug Oebalus ypsilongriseus was widespread in Florida rice fields. This was the first report of this species being found in commercial rice fields in the United States. Cherry and Nuessly (2010) reported that the stink bug Oebalus insularis is now widespread in Florida rice fields. This was the first report of this species being found in commercial rice fields in the United States. The stink bug complex attacking Florida rice is the most diversified and unique stink bug complex in US rice production. This 4-page fact sheet was written by Ron Cherry, and published by the UF Department of Entomology and Nematology, October 2013. http://edis.ifas.ufl.edu/in1009